Dental and maxillofacial features of condylo-mandibular dysplasia: A case series of 21 patients. Issue 10 (October 2020) - Bertin, Hélios; Merlet, Fanny-Laure; Khonsari, Roman-Hossein; Delaire, Jean; Corre, Pierre; Mercier, Jacques
Abstract: Introduction: Camel-hump condylo-mandibular dysplasia is a specific form of condyle dysostosis, first described by Delaire. The aim of this study was to describe the clinical and radiographic phenotype of the disease, and to discuss therapeutic options. Case series: Twenty-one patients were analyzed retrospectively. They exhibited the same unilateral facial asymmetry, which was of mandibular origin, with an elevated commissural line and occlusal cant, and a deviated chin on the side of the deformity. The soft tissues and the ears were always normal in terms of their physical appearance. Radiographic analysis generally revealed a short, curved, and anteriorly displaced condyle, with a high and sharp coronoid process. CT scans revealed that the glenoid fossa was empty. Twelve patients exhibited dental abnormalities, consisting mainly of dental inclusions affecting the lower first and/or second molars (10 patients). A good response to functional orthodontic treatment was achieved in eight patients, while 13 patients required a surgical mandibular lengthening procedure. Conclusion: Condylo-mandibular dysplasia is a congenital condyle deformity that needs to be recognized and differentiated from craniofacial microsomia in order to be able to provide patient-specific treatments.